2014
DOI: 10.1001/jamainternmed.2013.11349
|View full text |Cite|
|
Sign up to set email alerts
|

Association of β-Blocker Therapy With Risks of Adverse Cardiovascular Events and Deaths in Patients With Ischemic Heart Disease Undergoing Noncardiac Surgery

Abstract: IMPORTANCE Clinical guidelines have been criticized for encouraging the use of β-blockers in noncardiac surgery despite weak evidence. Relevant clinical trials have been small and have not convincingly demonstrated an effect of β-blockers on hard end points (ie, perioperative myocardial infarction, ischemic stroke, cardiovascular death, and all-cause death).OBJECTIVE To assess the association of β-blocker treatment with major cardiovascular adverse events (MACE) and all-cause mortality in patients with ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 24 publications
2
37
1
6
Order By: Relevance
“…Analysis of survival in death for 1 y showed that betablocker therapy can reduce the risk of death. This was consistent with other research that concluded in patients with CHD who underwent noncardiac surgery, beta-blockers can reduce the incidence of death and MACE significantly, especially in patients who have recently experienced a myocardial infarction and patients with heart failure [33]. Beta-blocker therapy in heart failure patients also proven to reduce the risk of sudden death from a cardiovascular event by 31%, 29% cardiovascular death and death from all causes by 33% [34].…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of survival in death for 1 y showed that betablocker therapy can reduce the risk of death. This was consistent with other research that concluded in patients with CHD who underwent noncardiac surgery, beta-blockers can reduce the incidence of death and MACE significantly, especially in patients who have recently experienced a myocardial infarction and patients with heart failure [33]. Beta-blocker therapy in heart failure patients also proven to reduce the risk of sudden death from a cardiovascular event by 31%, 29% cardiovascular death and death from all causes by 33% [34].…”
Section: Discussionsupporting
confidence: 91%
“…We identified all neuro, eye, ear-nose-throat, breast, orthopedic, abdominal, plastic, gynecological, endocrine, thoracic (noncardiac), urologic, and vascular surgeries requiring anesthesia performed between January 1, 2005, and November 30, 2011 (surgery codes are available in Table I in the Data Supplement). 5 We defined high-risk surgeries as intra-abdominal (excluding hernia repairs), intrathroacic, or suprainguinal aortic surgery, in accordance with the original classification.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of MI and major adverse cardiac events (MACE) significantly decreased in the beta-blocker group, only in patients with heart failure or recent MI (less than 2 years before surgery) (20). In a meta-analysis conducted by Wijeysundera in 2014, a moderate reduction was detected in the rate of MI (10).…”
Section: Effect On Myocardial Infarctionmentioning
confidence: 99%